Bio-inspired computing – theories and applications. 11th International Conference, BIC-TA 2016, Xi'an, China, October 28-30, 2016, Revised selected papers /: 11th International Conference, BIC-TA 2016, Xi'an, China, October 28-30, 2016, Revised selected papers. Part II : (2016) - Unknown
No abstract available